1993
DOI: 10.1159/000267332
|View full text |Cite
|
Sign up to set email alerts
|

Facial Parasympathetic Innervation of the Rat Choroid, Lacrimal Glands and Ciliary Ganglion

Abstract: The pterygopalatine parasympathetic innervation of the rat choroid, lacrimal glands and ciliary ganglion was ultrastructurally studied by anterograde 3H-leucine tracing. Numerous unmyelinated fibers and vesicle-containing terminals were labeled in these structures. No direct synaptic contacts were found. In the choroid, similar terminals were immunoreactive to vasoactive intestinal polypeptide (VIP). A regulatory feedback loop within the eye-related peripheral nervous system is endorsed by the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…The present study proves that in addition to para sympathetic innervation [9], the posterior eye segment receives sympathetic innervation like most parts of the anterior eye segment.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The present study proves that in addition to para sympathetic innervation [9], the posterior eye segment receives sympathetic innervation like most parts of the anterior eye segment.…”
Section: Discussionsupporting
confidence: 73%
“…The parasympathetic innervation of the an terior eye segment runs via the EdingerWestphal nucleus and the ciliary ganglion [8]. The parasympathetic innervation of the choroid, however, is thought to run via the pterygopalatine ganglion and to be of facial origin [9,10]. Physiological experiments also demonstrated sympathetic innervation of the choroid [11].…”
Section: Introductionmentioning
confidence: 99%
“…Physiological studies supported the functional nomenclature and showed that electrical stimuli in the region of the salivatory nuclei led to salivation (Wang and Borison, 1947). However, other studies showed that the parasympathetic ganglia innervated by SSN neurons project to the cerebral vasculature and lacrimal glands as well as to salivary glands Beckers et al, 1993;Cheng et al, 2000). Still other studies showed that some preganglionic neurons of the salivatory nuclei themselves participate in lacrimal rather than salivatory control (Toth et al, 1999).…”
Section: Discussionmentioning
confidence: 84%
“…In our study, however, we found that preganglionic neurons do not contain SOM. It is likely that other sources, such as the ciliary ganglion 20,[42][43][44] or fibers from other areas of the brain stem, 45 are the sources of the terminals described in the quail study. Although this discrepancy could be attributable to species differences, the fact that chickens and quails belong to the same family weakens this supposition.…”
Section: Central Nucleimentioning
confidence: 99%